Fundamentals of Entrepreneurship (ENT300) : Qushantek Makeover Service / Sharon Livan Ujang … [et al.] - Ujang, Sharon Livan; Jerry, Jane Effarenda; James, Vivian Urai; Samshulhana, Muhamad Shafiq (2019)
Qushantek Makeover Service offers service make up for customer, providing facial, grooming, eyebrow shaping, hairdo and also provide service to the customer's place. Our client is is customer identifying as middle and low class who want consume for service with affordable price. We also targeting students of UiTM and Unimas because they can have us to go to their place if they need make over of their occasion, but not to forget we also targeting business women where we believe they are very busy to come to our shop. , where we also provide service to their house.